Awareness of CSR activities among the employees of HSBC Bangladesh and a comparison with Dutch Bangla Bank Ltd. - Ahmed, Radiah Noor (BRAC University, 2011)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2010.